ANALISIS DESAIN SISTEM PENDATAAN FASILITAS DI PROGRAM STUDI UNIVERSITAS - Syirfa, Atika Naylatan; Dzune, Dzul Yaa; Salsabila, Carissa Octa; Prasetya, Randi Hindami; Zhydan, Zae; Wildani, Junaidah (Universitas Negeri Surabaya, 2023)
The research aims to analyze and design a campus facility management application system for the digital business program for students. The background of this research is the importance of having an efficient and integrated system to manage campus facilities in the context of the digital business program. The objectives of this study are to identify key issues in campus facility management, design a system that meets the needs of the digital business program, and test the successful implementation of the system. The research methodology includes system requirement analysis through primary and secondary data collection, identification and documentation of campus facility management processes, and system requirement analysis. The system design approach used is the Waterfall method, with sequential and structured development steps, incorporating several techniques: (1) use case diagrams and scenarios, (2) Sequence diagrams, (3) Activity diagrams. The results of this research include an integrated system design, including database design, intuitive user interface, and features such as facility registration, reservation, and availability monitoring. The system also allows students to submit repair requests and report facility damages. This research concludes that by implementing a facility management application system, the digital business program for students can be more efficient in managing campus facilities. This system enables real-time monitoring of facility availability, speeds up the reservation process, and improves responsiveness to repair requests.